1995
DOI: 10.1063/1.114313
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale formation of ultrasmooth surfaces on sapphire substrates for high-quality thin-film fabrication

Abstract: The atomically ultrasmooth surfaces with atomic steps of sapphire substrates were obtained by annealing in air at temperatures between 1000 and 1400 °C. The terrace width and atomic step height of the ultrasmooth surfaces were controlled on an atomic scale by changing the annealing conditions and the crystallographic surface of substrates. The obtained ultrasmooth surface was stable in air. The topmost atomic structure of the terrace was examined quantitatively by atomic force microscopy and ion scattering spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
221
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(230 citation statements)
references
References 0 publications
9
221
0
Order By: Relevance
“…We found that a small number of cycles of Ar + sputtering and annealing was sufficient to realize a clean Al 2 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that a small number of cycles of Ar + sputtering and annealing was sufficient to realize a clean Al 2 …”
Section: Discussionmentioning
confidence: 96%
“…Repeated iterations of Ar + sputtering and annealing are generally required to prepare a clean surface of TiO 2 (110) or other metal oxides. In the case of Al 2 O 3 (0001), however, we were able to achieve a periodic pattern of the Al 2 Keywords: sapphire, Al 2 O 3 (0001), non-contact atomic force microscopy, unit cell…”
mentioning
confidence: 96%
“…5) Prior to installing a substrate into the ultra-high vacuum PLD chamber, the substrate was cleaned with acetone and ethanol, and then dried in a stream of dry nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…1)4) In addition, atomically stepped sapphire substrates 5) have been applied for constructing nanostructures of inorganic materials 6), 7) and controlling molecular orientations of organic materials. 8) For high-performance mechanical, optical, and microelectronic applications, patterning the sapphire surface with features sized from the micrometer to nanometer scale is strongly desired.…”
Section: Introductionmentioning
confidence: 99%
“…• C for 5 h in air, they exhibited atomically flat surfaces [16]. The ILs were dropped with a micropipette (1 µl per droplet) on the substrates and no treatment was applied to spread them.…”
Section: High-throughput Experiments Inmentioning
confidence: 99%